A national scale floodplain model revealing channel gradient as a key determinant of beaver dam occurrence and inundation potential can anticipate land-use based opportunities and conflicts for river restoration - Matthew Dennis; Christof Angst; Joshua R. Larsen; Emmanuel Rey; Annegret Larsen (Global Ecology and Conservation)
The Eurasian beaver (Castor fiber) has expanded its range considerably due to reintroduction and conservation efforts and the species is now found in more than 30 countries across Europe. This expansion brings with it opportunities for nature restoration, the provision of river ecosystem services and the return of naturally functioning floodplains. It also has the potential for conflict with existing human land-use through dam induced floodplain inundation and wetland development. To maximise restoration benefits and minimise conflict, modelling approaches are needed that can predict the likelihood of dam building and include scenarios for subsequent floodplain inundation. This study describes the first national-scale comprehensive study on the drivers of beaver dam occurrence and beaver floodplain inundation potential. This revealed that channel gradient was the overriding driver of both dam occurrence and potential land-use impact. Although widely considered to be a key constraint, channel width exhibited considerably lower explanatory power. The delineation of areas reflecting overall opportunities and conflict reveals that the reintroduction of Castor fiber into Switzerland implies a net benefit from a landscape restoration perspective, though outcomes scaled closely with catchment position. Given the rapidly expanding population range and popularity of continuing beaver reintroductions, this approach could help maximise landscape restoration goals whilst minimising undesirable land-use conflicts that may harm conservation efforts.